2021
DOI: 10.1002/fes3.351
|View full text |Cite
|
Sign up to set email alerts
|

Drought and heat affect common bean minerals and human diet—What we know and where to go

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 296 publications
0
16
0
Order By: Relevance
“…Although its Latin and English names (Phaseolus vulgaris L.; common bean) suggest that it is an ordinary plant species, considering the nutritional properties and genetic structure of the common bean, it can be concluded that, on the contrary, it is an exceptional species that represents a potential crop for future food and nutrient security [10,11]. It originated in Mexico and, through later diversification and spread throughout the Americas and the world, has become the most ecologically adapted species of the genus Phaseolus, quickly becoming popular for its nutritional qualities [12].…”
Section: Common Bean Importancementioning
confidence: 99%
“…Although its Latin and English names (Phaseolus vulgaris L.; common bean) suggest that it is an ordinary plant species, considering the nutritional properties and genetic structure of the common bean, it can be concluded that, on the contrary, it is an exceptional species that represents a potential crop for future food and nutrient security [10,11]. It originated in Mexico and, through later diversification and spread throughout the Americas and the world, has become the most ecologically adapted species of the genus Phaseolus, quickly becoming popular for its nutritional qualities [12].…”
Section: Common Bean Importancementioning
confidence: 99%
“…Characterization of common beans low in PA ( lpa genotype) has recently attracted much attention. Specifically, stress-tolerance of lpa beans has become an interesting research focus ( Punjabi et al, 2018 ; Raboy, 2020 ; Losa et al, 2022 ). Lowering the phytate content in plants can potentially cause phenotypic changes as well as a loss of the antioxidative function of PA during abiotic stress conditions.…”
Section: Characterization Of Low Phytic Acid Bean ...mentioning
confidence: 99%
“…Production challenges associated with agro‐climate conditions cause yield losses of up to 80% under rain‐fed production systems (Beebe et al, 2013; Kazai et al, 2019). In sub‐Saharan Africa (SSA), where the cultivated area under common bean is currently estimated at 682,000 ha, the annual yield loss incurred due to drought/heat stress is significant and is estimated at 781,000 tonnes (Losa et al, 2022). The average yield of common bean in SSA is a paltry 600 kg ha −1 , compared with 1100 kg ha −1 in Brazil, 1700 kg ha −1 in China and 2000 kg ha −1 in the United States (Losa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In sub‐Saharan Africa (SSA), where the cultivated area under common bean is currently estimated at 682,000 ha, the annual yield loss incurred due to drought/heat stress is significant and is estimated at 781,000 tonnes (Losa et al, 2022). The average yield of common bean in SSA is a paltry 600 kg ha −1 , compared with 1100 kg ha −1 in Brazil, 1700 kg ha −1 in China and 2000 kg ha −1 in the United States (Losa et al, 2022). In SSA, bean production primarily relies on natural conditions with inadequate precipitation, low input application and devoid of irrigation facilities (Ramirez‐Villegas & Thornton, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation